Community responses during early phase of the COVID-19 epidemic in the Razavi Khorasan province of Iran: a cross-sectional study - Delshad, Mohammad Hossein; Pourhaji, Fatemeh (Acta Scientiarum. Health Sciences, 2024)
Community responses are important for the management of outbreaks during the early stages,when preventive interventions are the major options. Therefore, this study aims to investigate the behavioral responses of the community during the early phase of the A cross-sectional online survey was conducted after the confirmed COVID-19 in Iran. The research instrument was a demographic and risk perception questionnaire, and anxiety was assessed using the 7-item GAD scale. COVID-19 epidemic in Razavi Khorasan province of Iran. The population of the study consist of 500 residents of Razavi Khorasan who were randomly surveyed. The data was analyzed using the SPSS statistical version (V.20). The mean of age participants was 31.9 ± 11.9 years. The mean GAD-7 scores were 6.4 ± 5.2 and 92.4% of participants had moderate or severe anxiety (GAD-7 score ≥10). Many of the respondents reported their health status was very good or good (62.2 %; 311/500). About a quarter of them had respiratory symptoms in the last 14 days, and 20% of them had traveled outside the Razavi Khorasan province in the last month. The risk perception toward COVID-19 in the community of Razavi Khorasan province was moderate. Most participants are aware of the progression disease. This study suggested that timely behavioral assessment of the community is useful and effective to inform the next epidemic disease intervention, and risk communication strategies.